UPAYA PENINGKATAN STATUS KESEHATAN PADA BAYI DI MASA PANDEMI COVID-19 MELALUI IMUNISASI - Uswatun Hasanah; Yayuk Eliyana; Yulia Paramita Rusady (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
Immunization is a very efficient and effective public health program to prevent the occurrence of dangerous diseases. This activity aims to increase maternal and health cadre knowledge about immunization during the Covid-19 pandemic. So that the mother still wants to give complete immunizations to the baby and does not worry about coming to the health center or posyandu to the village hall to immunize the baby. In the end, the degree of health of infants can still be improved even though it is still the Covid-19 pandemic. This activity is carried out by providing education and training on all matters related to immunization during the Covid-19 pandemic. From the results of the evaluation of this activity it was found that there has been an increase in maternal and cadre knowledge about immunization during the pandemic. The hope of this activity is that immunization activities continue without any obstacles, where the mother still wants to bring her baby to be immunized and feel safe and comfortable.